Antimicrobial functions of EsLecH, a C-type lectin, via JNK pathway in the Chinese mitten crab, Eriocheir sinensis. (August 2016) - Zhu, You-Ting; Zhang, Xing; Wang, Shi-Chuang; Li, Wei-Wei; Wang, Qun
Abstract: C-type lectins (CTLs) are pattern recognition proteins that play significant roles in the innate immune system by identifying and eliminating pathogens. Here, we have reported a CTL ( Es LecH) from the Chinese mitten crab that can bind to microorganisms and regulate antimicrobial peptide (AMP) expression via the c-Jun N-terminal kinase (JNK) pathway. Es LecH was found to have an N-terminal signal peptide and a single carbohydrate recognition domain. The EsLecH transcript was detected abundantly in various tissues, and it was significantly upregulated in hemocytes after challenging with lipopolysaccharides and bacteria. Recombinant (r) Es LecH could bind to microorganisms, but at different levels. Ca 2+ significantly increased r Es LecH binding affinity to microorganisms. Furthermore, growth inhibition by r Es LecH increased with increasing r Es LecH levels. Knockdown of EsLecH was accompanied by a significant reduction in AMP expression and JNK phosphorylation; AMP expression was reduced with JNK silencing and can not rescued by r Es LecH when absence of JNK. These results indicate that Es LecH could regulate AMPs via JNK signaling. Highlights: We identified and characterized a C-type lectin, Es LecH, in Eriocheir sinensis . EsLecH was significantly upregulated in hemocytes exposed to LPS and bacteria. Es LecH could bind to a wide spectrum of microorganisms with distinct affinities. Es LecH positively regulated antimicrobial peptide expression via JNK pathway.